Cost awareness analysis on acute appendicitis treatment with social security agency for health (BPJS in health sector) at Budi Kemuliaan Hospital Batam - Anjari Wahyu Wardhani; Chriswardani Suryawati; Puji Harto (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Financial costs are recognized as one of the causes of lack of access to adequate health services, not least in the treatment of Acute Appendicitis with Social Security Agency for Health (BPJS in Health) in Budi Kemuliaan Hospital, Batam. Data describing health workers' awareness of costs is still limited. Increasing awareness of health workers can encourage increased treatment efficacy and reduce wasteful spending costs. This research aims to analyze the cost awareness of health workers' in the efficiency of Acute Appendicitis treatment.Methods: This research was a qualitative descriptive study accompanied by direct observation on the implementation of clinical pathways and SOP in cases of Appendicitis Acute in Budi Kemuliaan Hospital, Batam. In this study also conducted interviews involving nine main informants and three triangulation informants.Results: The average loss value Budi Kemuliaan Hospital in 2017 was Rp. 3,898,635, - and increased in 2018 to Rp.5,597,241,-. Low knowledge of health workers about case-mix which causes low cost awareness behavior. There was a low awareness of costs identified in the implementation of clinical pathways and SOP in cases of Appendicitis Acute in general surgeons, resulting in high financing. There was also low management monitoring. This has the potential to be a source of financial loss for hospitals.Conclusion: The lack of cost efficiency for Appendicitis Acute due to lack of cost awareness and monitoring of hospital management, so that it is necessary to carry out periodic monitoring related to the Cost awareness behavior of health workers. Keywords: cost awareness, Appendicitis Acute, Social Security Agency for Health, BPJS in Health, cost efficiencyReceived: 7 February 2019; Reviewed: 29 April 2019; Revised: 29 June 2019; Accepted: 29 June 2019 DOI: 10.35898/ghmj-32543